Clinical Hypnosis In Chronic Illness Management: A Scoping Review Protocol For Randomized Controlled Trial - Martaria Rizky Rinaldi; Gilles van Luijtelaar; Nida Ul Hasanat; Kwartarini Wahyu Yuniarti (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
This article outlines a protocol for conducting a scoping review on the use of clinical hypnosis in chronic illness management. Chronic diseases such as type 2 diabetes, cardiovascular disease, and cancer contribute significantly to global morbidity, mortality, and healthcare burden. While management strategies typically include medication, lifestyle changes, and psychological interventions, clinical hypnosis has emerged as a promising complementary approach. Clinical hypnosis, which involves techniques of deep relaxation, focused attention, and therapeutic suggestion, has shown potential in alleviating both psychological and physical symptoms associated with chronic illnesses. However, the body of evidence remains fragmented, particularly in terms of high-quality randomized controlled trials (RCTs). This scoping review aims to systematically map existing RCTs that examine the application of clinical hypnosis in chronic illness management. The protocol follows the PRISMA-ScR framework and will involve comprehensive searches across PubMed and Scopus. Studies will be included if they are RCTs involving adult patients with clinically diagnosed chronic illnesses and utilize clinical hypnosis as an intervention. Key data to be extracted include intervention characteristics, outcomes measured, and methodological features. The results of this review will identify current evidence trends, gaps in the literature, and implications for future research and clinical practice in the field of integrative chronic care.